Examining the relationship between perceived support and intention to quit directly and indirectly when mediated by affective commitment, organisational citizenship behaviour and job satisfaction - Kahumuza, Juliet (Organisational Psychology, 2015)
Includes bibliographical references (leaves 61-67).